Celiac disease: a comprehensive current review - Caio, Giacomo; Volta, Umberto; Sapone, Anna; Leffler, Daniel A.; De Giorgio, Roberto; Catassi, Carlo; Fasano, Alessio (BMC medicine, 2019)
Background Celiac disease remains a challenging condition because of a steady increase in knowledge tackling its pathophysiology, diagnosis, management, and possible therapeutic options. Main body A major milestone in the history of celiac disease was the identification of tissue transglutaminase as the autoantigen, thereby confirming the autoimmune nature of this disorder. A genetic background ( HLA-DQ2/DQ8 positivity and non-HLA genes) is a mandatory determinant of the development of the disease, which occurs with the contribution of environmental factors (e.g., viral infections and dysbiosis of gut microbiota). Its prevalence in the general population is of approximately 1%, with female predominance. The disease can occur at any age, with a variety of symptoms/manifestations. This multifaceted clinical presentation leads to several phenotypes, i.e., gastrointestinal, extraintestinal, subclinical, potential, seronegative, non-responsive, and refractory. Although small intestinal biopsy remains the diagnostic ‘gold standard’, highly sensitive and specific serological tests, such as tissue transglutaminase, endomysial and deamidated gliadin peptide antibodies, have become gradually more important in the diagnostic work-up of celiac disease. Currently, the only treatment for celiac disease is a life-long, strict gluten-free diet leading to improvement in quality of life, ameliorating symptoms, and preventing the occurrence of refractory celiac disease, ulcerative jejunoileitis, and small intestinal adenocarcinoma and lymphoma. Conclusions The present review is timely and provides a thorough appraisal of various aspects characterizing celiac disease. Remaining challenges include obtaining a better understanding of still-unclear phenotypes such as slow-responsive, potential (minimal lesions) and seronegative celiac disease. The identification of alternative or complementary treatments to the gluten-free diet brings hope for patients unavoidably burdened by diet restrictions.